Menstrual hygiene practice and associated factors among adolescent primary school females in Dale Woreda, Sidama, Ethiopia: a cross sectional study - Ayele, Amanuel; G/Mariam, Meskerem; Beyene, Hunachew; Tolcha, Alemu; Tediso, Dansamo; Shalamo, Teshale; Belayneh, Teshale (Frontiers in Reproductive Health, 2025)
BackgroundDespite poor menstrual hygiene practices exposing adolescent females to reproductive health problems, it has not been adequately studied in low-income countries. Due to a lack of proper information, the majority of teenage girls enter puberty without having prepared themselves. The aim of this study was to assess menstrual hygiene practice and associated factors among adolescent female students.MethodsAn institution-based cross-sectional study design was employed from March 10 to April 20, 2022. A random sample of 608 adolescent female students was included in the study. A multistage sampling was applied to employee study participants. Data were collected using a structured questionnaire administered through an interview technique. A logistic regression model was used to analyze the data using version 26 SPSS statistical software. Descriptive statistics were used to summarize the data. An adjusted odds ratio with a 95% confidence interval and a corresponding p-value <0.05 was used to measure the strength of association.ResultThe prevalence of poor menstrual hygiene practices among adolescent girls was 28.4%. Poor knowledge of adolescent girls [AOR = 2.64, 95% CI: 1.74, 4.02], mothers' educational level [AOR = 0.86, 95% CI: 0.79, 0.94], fathers' occupation of private employers and daily laborers [AOR = 3.1, 95% CI: 1.46, 6.69] and [AOR = 1.98, 95% CI: 1.03, 3.8], and having hand washing facilities [AOR = 0.51, 95% CI: 0.34, 0.77] were significantly associated with poor menstrual hygiene management practices among adolescent schoolgirls.ConclusionIn this study, we determined the level of poor menstrual hygiene practice. We identified factors significantly associated with menstrual hygiene practices. Interventions should focus on creating awareness among adolescent girls, providing menstrual hygiene management facilities, and improving the educational and occupational levels of parents.